Gurjanovometopa onenusica gen. nov., sp. nov. (Crustacea: Amphipoda: Stenothoidae) from the Russian coasts of the Sea of Japan - Labay, Vjacheslav S. (Zootaxa, 2025)
The new genus of stenothoid amphipod Gurjanovometopa and new species G. onenusica are described from the shelf of south-western Sakhalin Island. The genus Gurjanovometopa gen. nov. differs from the other genera of the family Stenothoidae by the specific structure of gnathopod 1 (simple, merus and carpus with long narrow posterodistal lobe each, propodus elongated almond-shaped, without palmar margin) in combination with subchelate gnathopod 2.